'Who's Not Afraid of ISIS?'. Issue 1 (2nd January 2018) - Combes, M. L. deRaismes
ABSTRACT: This paper explores the politics of fear surrounding the construction of ISIS as an existential threat in American political speech. It does so by pointing out the unreflexive nature of both first-order characterisations of ISIS and second-order explanations of those claims. Namely, both draw on fear's utility without questioning the latent assumptions rooted in that instrumentalisation. Asking who's not afraid of ISIS attempts to disrupt such assumptions. Two groups present themselves: sympathisers and those asserting that the threat is overblown. Upon closer inspection, however, both narratives still remain firmly entrenched within the same fear doxology they purportedly challenge. I discuss the difficulty of contesting the fear/utility nexus and posit that perhaps the truly doxic dimension of the ISIS narrative is fear's 'representativeness', its shorthand set of meanings that sustain a causal vision of violence meant to propagate the fantasy of a knowable world.